ANALISIS YURIDIS TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA SECARA MELAWAN HUKUM (Studi Kasus 84/Pid.Sus/2023/PN Mdn - Silaban, Dandy; Feby Florenza Br Sembiring; Annisa Puspitasari; Parlaungan Gabriel Siahaan; Dewi Pika Lumban Batu (PPKn, Fakultas Keguruan dan Ilmu Pengetahuan Universitas Palangka Raya, 2023)
Crimes whose perpetrators are subject to universal principles, which can be described as acts or crimes that are categorized as crimes against the enemy of humanity, include: narcotics crimes, terrorism, airplane hijacking, genocide, etc. This research contains narcotics crimes with Decision Number 84/Pid.Sus/2023/PN Mdn. This research uses secondary data or library materials only. This research is included in the library research category. The problem that the author wants to study is the stages of implementation of the decision process in case number 84/Pid.Sus/2023/PN Mdn. Declare that the defendant Eriko Alias Eko has been legally and convincingly proven guilty of committing the crime of